Tobyhanna Overhauls Air Force Training Tool - Boucher, Jacqueline (2013)
It was 20 degrees below zero when personnel fielded Tobyhanna Army Depot's first overhauled Unmanned Threat Emitter training system at Eielson Air Force Base, Alaska. Overhaul work on the Air Force UMTE systems began in November 2011, with the first system being completed in February. Personnel are working on three more systems, each at different phases of the repair process, in the Tactical End Item Repair Facility. The UMTE is an U.S. Air Force aircrew training system that is environmentally rugged, unmanned and remotely operable. It is capable of radiating threat signals that simulate surface-to-air missiles and anti-aircraft artillery radar, and can be airlifted to various training sites. There are 35 systems in the inventory, 16 of which reside on the Joint Pacific Alaska Range Complex. The JPARC is the world's largest instrumented air combat training range with over 67,000 square miles of airspace and is the venue for RED FLAG-Alaska. Published in Army Communicator, p38-40, Summer 2013.